Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.4314/sajas.v37i4.4101
|View full text |Cite
|
Sign up to set email alerts
|

On the suitability of Illius and Gordon\'s model for simulating the intake and digestibility of roughage diets by ruminants

Abstract: ________________________________________________________________________________ AbstractThe aim of this study was to evaluate the suitability of Illius and Gordon's simulation model for predicting the digestibility and intake of tropical roughages by ruminants. Data from seven suitable empirical studies (i.e. studies that reported all requisite data needed to run the model) in which tropical roughages were fed to ruminants were used. These seven studies had 235 intake and 70 digestibility measurements on goat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
(48 reference statements)
0
14
1
Order By: Relevance
“…Lechner-Doll et al [21] added that selective retention of particles is more pronounced in cattle than in sheep suggesting that the passage rate of large particles is greater in sheep than in cattle. Outflow rates of fine solid material are normally estimated by allometric procedures as an inverse function of body weight, which infers erroneously that the rate of passage in smaller ruminants is always greater than that in larger ruminants [1]. Parra [22] showed higher passage rates for smaller herbivores than larger herbivores with diet quality held constant.…”
Section: Animal Species and Feeding Typesmentioning
confidence: 99%
See 4 more Smart Citations
“…Lechner-Doll et al [21] added that selective retention of particles is more pronounced in cattle than in sheep suggesting that the passage rate of large particles is greater in sheep than in cattle. Outflow rates of fine solid material are normally estimated by allometric procedures as an inverse function of body weight, which infers erroneously that the rate of passage in smaller ruminants is always greater than that in larger ruminants [1]. Parra [22] showed higher passage rates for smaller herbivores than larger herbivores with diet quality held constant.…”
Section: Animal Species and Feeding Typesmentioning
confidence: 99%
“…This is partly due to limited information on the critical factors that affect intake, passage rates of digesta and rumen fill for goats. Nsahlai and Apaloo [1] examined the appropriateness of model in [2] to predict the intake in ruminants grazing on poor quality roughages in tropical regions and showed that the model, though structurally adequate, underestimated roughage intake, partly due to poor estimates of gut fill and rate of passage. Similarly, the authors [3][4][5] showed that the model of Illius and Gordon [2] overestimated retention time in browsing ruminants for particle sizes less than 2 mm.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations